Thrombocytopenia in Newborn with Holt-Oram Syndrome: A Rare Case Report - Sah, Manish; Shah, Raj Kumar; Gauchan, Eva (Nepal Journal of Medical Sciences, 2024)
Holt-Oram syndrome or heart-hand syndrome is a rare congenital disorder characterized by a combination of upper limb abnormalities and congenital heart lesions. We report a case of a neonate with congenital anomalies of the left upper limb (radial club hand, absent radius bone, and absent thumb) with multiple cardiac defects (atrial septal defect, ventricular septal defect, and patent ductus arteriosus). This case report emphasizes the need for screening of cardiac anomalies in all newborns with upper limb deformities.